Comparison of pull-out bond strength and microleakage of lithium disilicate onlay with and without immediate dentin sealing - Aruna Krishnan; Nishitha Arun; Mohammad Fareed; Nisha Manila; Mohmed Isaqali Karobari (Journal of Applied Biomaterials & Functional Materials)
Background: Effective adhesion between dentin and resin materials is essential for the long-term durability of onlays, as the strength and durability of the tooth-restoration complex hinge on reliable adhesion. This study aims to enhance the adhesion of lithium disilicate onlays by employing immediate dentin sealing (IDS) and evaluates its effectiveness by comparing pull-out bond strength and microleakage with and without IDS. Methods: Extracted human premolars were prepared and categorized into two distinct groups: Group A (with IDS) and Group B (without IDS). In Group A, the dentin surfaces were sealed immediately after tooth preparation using an adhesive resin. In Group B, no sealing was performed before bonding the lithium disilicate restorations. Pull-out bond strength was assessed utilizing universal testing machine. Microleakage was evaluated through dye penetration analysis after thermocycling and sectioning of the samples. For statistical interpretation, one-way ANOVA followed by Tukey’s post-hoc test was applied. Results: The pull-out bond strength was significantly higher in Group A compared to Group B ( p  = 0.0001). Microleakage evaluation revealed less dye penetration in Group A, indicating superior marginal integrity with IDS. The high-resolution images provided clearer visualization of the interfaces and the extent of dye penetration. Conclusion: Immediate dentin sealing significantly enhances the pull-out bond strength of lithium disilicate onlay and reduces microleakage. These findings suggest that IDS is a beneficial step in the bonding protocol for lithium disilicate restorations, potentially improving the longevity and performance of the restorations.